2015
DOI: 10.3389/fpsyg.2015.00603
|View full text |Cite
|
Sign up to set email alerts
|

Network-based characterization of brain functional connectivity in Zen practitioners

Abstract: In the last decade, a number of neuroimaging studies have investigated the neurophysiological effects associated with contemplative practices. Meditation-related changes in resting state functional connectivity (rsFC) have been previously reported, particularly in the default mode network, frontoparietal attentional circuits, saliency-related regions, and primary sensory cortices. We collected functional magnetic resonance imaging data from a sample of 12 experienced Zen meditators and 12 meditation-naïve matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 56 publications
4
31
2
Order By: Relevance
“…IC23, another marginally Suppression-related component, was the only one that significantly involved the insular cortices. This insular activation has been reported in both thought suppression and inhibition studies (Krmpotich et al 2013;Kemmer et al 2015;Lin et al 2015;Rigon et al 2015) but lacks an established interpretation. This area has been implicated in a wide variety of functions (Corbetta et al 1998), including mental imagery (Mellet et al 1996;Kosslyn and Thompson 2003;Ganis et al 2004;Mazard et al 2004;Sack et al 2008).…”
Section: Visual and Other Networkmentioning
confidence: 69%
“…IC23, another marginally Suppression-related component, was the only one that significantly involved the insular cortices. This insular activation has been reported in both thought suppression and inhibition studies (Krmpotich et al 2013;Kemmer et al 2015;Lin et al 2015;Rigon et al 2015) but lacks an established interpretation. This area has been implicated in a wide variety of functions (Corbetta et al 1998), including mental imagery (Mellet et al 1996;Kosslyn and Thompson 2003;Ganis et al 2004;Mazard et al 2004;Sack et al 2008).…”
Section: Visual and Other Networkmentioning
confidence: 69%
“…The inconsistency across findings that is typical for this literature is well illustrated by the three significant findings identified for FC between the default and executive networks. Whereas two studies found increased FC between the dlPFC and regions of the default network (PCC and mPFC/ACC, respectively), one study using independent component analysis found decreased FC between the entire default and executive networks . These findings are not exact contradictions, but the pattern of both increased and decreased FC is difficult to reconcile.…”
Section: Mindfulness and Functional Connectivitymentioning
confidence: 95%
“…Whereas two studies found increased FC between the dlPFC and regions of the default network (PCC and mPFC/ACC, respectively), one study using independent component analysis found decreased FC between the entire default and executive networks. 25,27,79 These findings are not exact contradictions, but the pattern of both increased and decreased FC is difficult to reconcile. A likely explanation for this divergence is the diversity of methods employed.…”
Section: Mindfulness and Functional Connectivitymentioning
confidence: 98%
“…31), recent cross-sectional fc studies of meditators have generally demonstrated increased connectivity between the two main nodes of the DMN (PCC and vmPFC) and between nodes of the DMN and salience and executive networks during a nonmeditative resting state. 109,111,114,[129][130][131][132] These studies reflect changes that are sustained in nonmeditative states. In a small number of studies, increased fc has been found between DMN nodes and task-positive regions (e.g., dACC, dlPFC) during and across styles of meditation practice (Fig.…”
Section: Mindful Awareness and Discernment Versus Mind Wandering And mentioning
confidence: 97%